1947
DOI: 10.2134/agronj1947.00021962003900110003x
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Seed Treatment of Flax1

Abstract: H IGH germinating power of the seed is one among several important factors in obtaining a good stand of flax. The viability of Kansas-grown flaxseed, some of the causes of low germination, and the effect of treating seed on emergence and yield are discussed in this paper. REVIEW OF LITERATURE Landon (I I) 3 stated that good flax seed should have a germination of more than 95%. He stated further that flax seed was more subject to weather damage than wheat or oats, and in some years the weather conditions at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1958
1958
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In the non-autoclaved soil, microorganisms would have been present and could have infected the germinating seed, killing the developing seedling. This is consistent with our knowledge of soilborne microorganisms reducing the germination and seedling stands of flax (Reitz et al 1947;Kommedahl et al 1955;Groth et al 1970).…”
Section: Discussionsupporting
confidence: 92%
“…In the non-autoclaved soil, microorganisms would have been present and could have infected the germinating seed, killing the developing seedling. This is consistent with our knowledge of soilborne microorganisms reducing the germination and seedling stands of flax (Reitz et al 1947;Kommedahl et al 1955;Groth et al 1970).…”
Section: Discussionsupporting
confidence: 92%
“…Culbertson and Kommedahl (1956), Culbertson et al (1960) and Comstock et al (1963) all found that yellow-seeded lines of flax had lower seed yield but higher oil concentration than brown-seeded lines. Reitz et al (1947) had found that the lower seed yield of yellow-seeded flax was associated with lower seed germination and poor stands. A slight but significantly later maturity for yellow-seeded lines when compared with the brown-seeded lines also was reported by Culbertson et al (1960).…”
mentioning
confidence: 99%